2017
DOI: 10.5194/gmd-10-4229-2017
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the wind farm parameterization in the Weather Research and Forecasting model (version 3.8.1) with meteorological and turbine power data

Abstract: Abstract. Forecasts of wind-power production are necessary to facilitate the integration of wind energy into power grids, and these forecasts should incorporate the impact of windturbine wakes. This paper focuses on a case study of four diurnal cycles with significant power production, and assesses the skill of the wind farm parameterization (WFP) distributed with the Weather Research and Forecasting (WRF) model version 3.8.1, as well as its sensitivity to model configuration. After validating the simulated am… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 61 publications
(69 reference statements)
2
49
0
Order By: Relevance
“…During this period, a lack of major synoptic events allowed strong nightly nocturnal low-level jets to occur (Vanderwende et al, 2015). Lee and Lundquist (2017a) found that WRF performed well in capturing the timing, intensity, and position of these low-level jets. Furthermore, the wind turbines operated without curtailment, and the instruments were online collecting data, making this period ideal for a model sensitivity and performance evaluation.…”
Section: Specific Examples Includementioning
confidence: 91%
See 2 more Smart Citations
“…During this period, a lack of major synoptic events allowed strong nightly nocturnal low-level jets to occur (Vanderwende et al, 2015). Lee and Lundquist (2017a) found that WRF performed well in capturing the timing, intensity, and position of these low-level jets. Furthermore, the wind turbines operated without curtailment, and the instruments were online collecting data, making this period ideal for a model sensitivity and performance evaluation.…”
Section: Specific Examples Includementioning
confidence: 91%
“…Past studies have begun evaluating this sensitivity in the WRF WFP. Lee and Lundquist (2017a) note that a ∼12-m vertical resolution is necessary to reproduce observed power production, while Mangara et al (2019) find that the wake dynamics simulated by the WFP are more sensitive to horizontal resolution than vertical resolution. Xia et al (2019) find differences in the WFP solution of surface temperature changes depending on the inclusion of the turbine-generated TKE term.…”
Section: Specific Examples Includementioning
confidence: 99%
See 1 more Smart Citation
“…We use the wind farm parameterization (WFP) of Fitch et al (2012) to simulate the interaction between atmosphere and wind farms. The WFP extracts kinetic energy from the mean flow and acts as a source of turbulence, depending on the thrust and power coefficients of the installed turbines in the model (Fitch et al 2012, Jiménez et al 2015, Lee and Lundquist 2017. Therefore, the WFP interacts with the planetary boundary layer scheme of Nakanishi and Niino (2004) that we use in all three domains.…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…The vertical direction is discretized with 100 grid cells in all the domains. The grid points are clustered near the surface and in the rotor region where the resolution is between 7 and 12 m. Lee et al 21 showed that a resolution of 12 m near the surface is sufficient to obtain good agreement with the observed wind speed, wind direction, and power production. The turbines are modeled as a momentum sink (drag) and turbulent kinetic energy source as in Fitch et al 2 The drag generated by the turbine in a grid cell is given by…”
Section: Experimental Measurementsmentioning
confidence: 99%